2013
DOI: 10.1016/j.ijnonlinmec.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of internal-heating on weakly non-linear stability analysis of Rayleigh–Bénard convection under g-jitter

Abstract: a b s t r a c tIn this paper, we study the combined effect of internal-heating and time-periodic gravity modulation on thermal instability in a viscous fluid layer, heated from below. The time-periodic gravity modulation, considered in this problem can be realized by vertically oscillating the fluid layer. A weak non-linear stability analysis has been performed by using power series expansion in terms of the amplitude of gravity modulation, which is assumed to be small. The Nusselt number has been obtained in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…Thus, related to gravity modulation, the studies by Gresho and Sani [8] and Clever et al [9] showed that the gravity modulation acts on the entire volume of fluid and may have a stabilizing or destabilizing effect depending on the amplitude and frequency of the forcing. Similar studies related to gravity modulation were done by Malashetty and Padmavathi [10] , Yang [11] , Bhadauria et al [12] , Bhadauria [13] , Bhadauria et al [14] , Bhadauria and Kiran [15][16] , Bhadauria et al [17] , and Kiran [18] .…”
Section: Introductionsupporting
confidence: 74%
“…Thus, related to gravity modulation, the studies by Gresho and Sani [8] and Clever et al [9] showed that the gravity modulation acts on the entire volume of fluid and may have a stabilizing or destabilizing effect depending on the amplitude and frequency of the forcing. Similar studies related to gravity modulation were done by Malashetty and Padmavathi [10] , Yang [11] , Bhadauria et al [12] , Bhadauria [13] , Bhadauria et al [14] , Bhadauria and Kiran [15][16] , Bhadauria et al [17] , and Kiran [18] .…”
Section: Introductionsupporting
confidence: 74%
“…The effect of increasing Pr for lower values there is enhancement in the heat and mass transfer further increment in it no effect is found (Bhadauria et al 2013, Bhadauria andKiran 2014a,f …”
Section: Discussionmentioning
confidence: 96%
“…studied thermally or gravity modulated non-linear stability problem in a rotating viscous fluid layer, using Ginzburg-Landau equation for stationary mode of convection. Bhadauria et al (2013) studied internal heating effects weak nonlinear Rayleigh-Bénard convection under gravity modulated, using Ginzburg-Landau equation for stationary mode of convection.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on internal heating is much less extensive than that on external heating. Some latest studies are due to Bhadauria et al [22], Bhadauria [23] and Bhadauria et al ([24], [25], [26]). …”
Section: Introductionmentioning
confidence: 99%